Effects of Two Calcium Silicate Cements on Transforming Growth Factor-β1 Secretion from Human Dental Pulp Stem Cells - Omidi, Salma; Bagheri, Mehdi; Fazli, Mozhgan; Ahmadiankia, Naghmeh (Iranian Endodontic Journal, 2018)
Introduction: The aims of this in vitro study were to evaluate the effects of two calcium silicate based cements, Calcum-enriched Mixture (CEM) and Biodentine on proliferation of human dental pulp stem cells (hDPSCs) and the effects of proposed cements on the secretion of Transforming Growth Factor β1 (TGF-β1). Methods and materials: The cell cultures of human Dental Pulp Stem Cells (hDPSCs) at passage 3-5 were treated with various dilutions (1/1, 1/2, 1/4, 1/8, 1/16, and 1/32) of CEM and Biodentine extracts to assess the cell proliferation using 3-(4, 5-dimethylthiazol-2-Y1)-2, 5-diphenyltetrazolium brovide (MTT) assay after 48 and 72 h. The amount of TGF-β 1 secretion were estimated after 72 h using an enzyme-linked immunosorbent assay. Data were analyzed using the one-way analysis of variance (ANOVA) followed by the Dunnett’s test at the level of significance set at 0.05. Result: CEM showed the highest rates of cell proliferation compared to Biodentine after 72 h (P<0.05). A greater amount of TGF-β1 was secreted by hDPSCs treated with Biodentine compared to CEM (P<0.05). These differences were statistically significant (P<0.05). Conclusion: In this in vitro study hDPSCs showed more proliferation capacity with CEM rather than Biodentine and TGF-β1 secretion rate in Biodentine was higher. Keyword: Biodentine; Calcium-Enriched Mixture; Human Dental Pulp Stem Cells; Proliferation; Transforming Growth Factor-β1